Biosorption study of amaranth dye removal using Terminalia chebula shell, Peltophorum pterocarpum leaf and Psidium guajava bark. Issue 10 (24th August 2022) - Malleswari, P. V. N.; Swetha, S.; Jegadeesan, Gautham B.; Rangabhashiyam, S.
Abstract: Amaranth dye (AD) is trisodium (4E)-3-oxo-4-[(4-sulfonato-1- naphthyl) hydrazono] naphthalene-2, 7-disulfonate and anionic in nature. In the present investigation, waste biomasses such as Terminalia chebula shell (TCS), Peltophorum pterocarpum leaf (PPL) and Psidium guajava bark (PGB) are explored as biosorbents for the first time toward the removal of AD from aqueous solution in a batch method. Influence of biosorption parameters such as pH, initial concentration of AD, biosorbents (TCS, PPL, PGB) dosage, temperature and contact time was studied. Biosorption equilibrium data was analyzed using two parameter isotherms. The kinetics of the biosorption process was analyzed using different models to understand the rate-determining step. The results of the biosorption experiment and modeling investigation illustrated that the pseudo-second-order rate equation fits the experimental data and further the experimental results showed Langmuir isotherm fitted well the biosorption equilibrium data. TCS showed more efficiency toward the removal of AD than PPL and PGB. The value of enthalpy for TCS is 1.527 kJ/mol suggests that the AD removal process is endothermic. The positive value of entropy is 6.429 J/mol K indicates that the particle is randomly disordered and negative values of standard Gibbs free energy (Δ G °) suggested that the biosorption process is spontaneous. Novelty statement: Biomasses of Terminalia chebula shell (TCS), Peltophorum pterocarpum leaf (PPL) and Psidium guajava bark (PGB) reported as first time explored biosorbent for amaranth dye (AD) removal from aqueous solution. Optimal biosorption parameter for AD removal determined. Experimental data examined using isotherm, kinetic and thermodynamic analysis.